In Vivo Risk Analysis of Pancreatic Cancer Through Optical Characterization of Duodenal Mucosa. Issue 5 (July 2015) - Mutyal, Nikhil N.; Radosevich, Andrew J.; Bajaj, Shailesh; Konda, Vani; Siddiqui, Uzma D.; Waxman, Irving; Goldberg, Michael J.; Rogers, Jeremy D.; Gould, Bradley; Eshein, Adam; Upadhye, Sudeep; Koons, Ann; et al.
Abstract : Objectives: To reduce pancreatic cancer mortality, a paradigm shift in cancer screening is needed. Our group pioneered the use of low-coherence enhanced backscattering (LEBS) spectroscopy to predict the presence of pancreatic cancer by interrogating the duodenal mucosa. A previous ex vivo study (n = 203) demonstrated excellent diagnostic potential: sensitivity, 95%; specificity, 71%; and accuracy, 85%. The objective of the current case-control study was to evaluate this approach in vivo. Methods: We developed a novel endoscope-compatible fiber-optic probe to measure LEBS in the periampullary duodenum of 41 patients undergoing upper endoscopy. This approach enables minimally invasive detection of the ultrastructural consequences of pancreatic field carcinogenesis. Results: The LEBS parameters and optical properties were significantly altered in patients harboring adenocarcinomas (including early-stage) throughout the pancreas relative to healthy controls. Test performance characteristics were excellent with sensitivity = 78%, specificity = 85%, and accuracy = 81%. Moreover, the LEBS prediction rule was not confounded by patients' demographics. Conclusion: We demonstrate the feasibility of in vivo measurement of histologically normal duodenal mucosa to predict the presence of adenocarcinoma throughout the pancreas. This represents the next step in establishing duodenal LEBS analysis as a prescreening technique that identifies clinically asymptomatic patients who are at elevated risk of PC.